2004
DOI: 10.1074/jbc.m400491200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Dioxygen-bound Heme Oxygenase from Corynebacterium diphtheriae

Abstract: HmuO, a heme oxygenase of Corynebacterium diphtheriae, catalyzes degradation of heme using the same mechanism as the mammalian enzyme. The oxy form of HmuO, the precursor of the catalytically active ferric hydroperoxo species, has been characterized by ligand binding kinetics, resonance Raman spectroscopy, and x-ray crystallography. The oxygen association and dissociation rate constants are 5 M ؊1 s ؊1 and 0.22 s ؊1 , respectively, yielding an O 2 affinity of 21 M ؊1 , which is ϳ20 times greater than that of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
171
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(178 citation statements)
references
References 57 publications
7
171
0
Order By: Relevance
“…The increased hydrophobicity of the active site upon the exclusion of water would also aid the stabilization of an oxyferrous species. Studies with heme oxygenase suggest that the hydrogen-bonding interactions to the dioxygen substrate may also help to prevent its heterolysis (20), and the exclusion of water probably removes a hydrogen-bond competitor to the dioxygen. After the initial attack by the C3 atom, the reaction may proceed via a Criegee rearrangement or a dioxetane intermediate (SI Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The increased hydrophobicity of the active site upon the exclusion of water would also aid the stabilization of an oxyferrous species. Studies with heme oxygenase suggest that the hydrogen-bonding interactions to the dioxygen substrate may also help to prevent its heterolysis (20), and the exclusion of water probably removes a hydrogen-bond competitor to the dioxygen. After the initial attack by the C3 atom, the reaction may proceed via a Criegee rearrangement or a dioxetane intermediate (SI Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, we failed to confirm this, and rather found that these two residues affected neither the binding to CPR nor the NADPH-CPR-supported HO activity. Yoshida's group also showed that replacement of Lys 18 and Lys 22 with Ala did not affect the reduction rate of the heme bound to HO-1 (66). As described above, our docking model shows a close contact between Lys 149 in the distal F helix of HO-1 and the acidic clusters near the FMN site of CPR (Fig.…”
Section: Single Turnover Reactions Of Heme Complexes Of Ho-1 Mutants-mentioning
confidence: 99%
“…The FMN domain of CPR is of particular importance for interaction with redox partners, because FMN acts as the exit point of electrons to heme. Interestingly, the FRET study showed that Lys 18 and Lys 22 in the proximal A helix of HO-1 are involved in the interaction with CPR (50). However, we failed to confirm this, and rather found that these two residues affected neither the binding to CPR nor the NADPH-CPR-supported HO activity.…”
Section: Single Turnover Reactions Of Heme Complexes Of Ho-1 Mutants-mentioning
confidence: 99%
“…Dioxygen-bound cdHO has two strong hydrogen bonds that can preferentially stabilize the highly polar Fe⅐O 2 complex (29). One interaction is with the amide NH of Gly-139, and the other is with the distal pocket water molecule.…”
mentioning
confidence: 99%
“…The greater polarity of the bound O 2 ligand also plays a role in enhancing the affinity of O 2 relative to CO for both the globins and HO enzymes. The partition constant (M), defined as the ratio of the equilibrium association constants for CO and O 2 (K CO /K O2 ), is ϳ30,000 for free heme, whereas that for sperm whale myoglobin is only ϳ40 and is further reduced to ϳ4 for human heme oxygenase (28,29). The O 2 affinities of mammalian HO-1 and HO-2 are 30 -90-fold higher than those of mammalian myoglobins (28), whereas the O 2 affinity of the bacterial HO from C. diphtheriae is 20-fold higher than that of myoglobin (29).…”
mentioning
confidence: 99%